Absence of microsatellite instability and BRAF (V600E) mutation in testicular germ cell tumors - Cárcano, F. M. (2016)
Testicular germ cell tumors (TGCT) are the most common malignant neoplasm in young men. DNA mismatch repair deficiency can lead to microsatellite instability (MSI), an important mechanism of genetic instability. A mutation of the BRAF gene has been implicated in the pathogenesis of several solid tumors and has recently become an important therapeutic target. The role of MSI and BRAF gene mutation in TGCT, particularly in refractory disease, is poorly understood and reported findings are controversial. In this study, we aimed to determine the frequency and clinical impact of MSI status and BRAF mutations in TGCT. DNA was isolated from formalin-fixed paraffin embedded (FFPE) tissue from 150 TGCT cases. The MSI phenotype was evaluated using multiplex PCR for five quasimonomorphic mononucleotide repeat markers. Exon 15 of the BRAF oncogene (V600E) was analyzed by PCR, followed by direct sequencing. Sixteen percent of cases were considered to have refractory disease. In a small subset of cases (17 for MSI and 18 for BRAF), the quantity and quality of DNA recovery were poor and therefore, were unable to be analyzed. The remaining 133 TGCT cases showed a complete absence of MSI. Of the 132 cases successfully evaluated for BRAF mutations, all were V600E wild-type. In conclusion, despite a distinct response of testicular germ cell tumors to therapy, microsatellite instability, and the BRAF V600E mutation were absent in all testicular germ cell tumors tested in this study.